MaNGA DynPop – IV. Stacked total density profile of galaxy groups and clusters from combining dynamical models of integral-field stellar kinematics and galaxy–galaxy lensing - Wang, Chunxiang; Li, Ran; Zhu, Kai; Shan, Huanyuan; Xu, Weiwei; Cappellari, Michele; Gao, Liang; Li, Nan; Lu, Shengdong; Mao, Shude; Yao, Ji; Xie, Yushan (Monthly Notices of the Royal Astronomical Society, 2024)
We present the measurement of total and stellar/dark matter decomposed mass density profile around a sample of galaxy groups and clusters with dynamical masses derived from integral-field stellar kinematics from the MaNGA survey in Paper I and weak lensing derived from the DECaLS imaging survey. Combining the two data sets enables accurate measurement of the radial density distribution from several kpc to Mpc scales. Intriguingly, we find that the excess surface density derived from stellar kinematics in the inner region cannot be explained by simply adding an NFW dark matter halo extrapolated from lensing measurement at a larger scale to a stellar mass component derived from the NASA-Sloan Atlas (NSA) catalogue. We find that a good fit to both data sets requires a stellar mass normalization about three times higher than that derived from the NSA catalogue, which would require an unrealistically too-heavy initial mass function for stellar mass estimation. If we keep the stellar mass normalization to that of the NSA catalogue but allow a varying inner dark matter density profile, we obtain an asymptotic slope of γ gnfw = 1.82+0.15 −0.25 and γ gnfw = 1.48+0.20 −0.41 for the group bin and the cluster bin, respectively, significantly steeper than the NFW case. We also compare the total mass inner density slopes with those from TNG300 and find that the values from the simulation are lower than the observation by about 2σ level.